Cis‐control of Six1 expression in neural crest cells during craniofacial development. Issue 12 (16th September 2019) - Wu, Zhaoming; Rao, Yanxia; Zhang, Sushan; Kim, Eun‐Jung; Oki, Shinya; Harada, Hidemitsu; Cheung, Martin; Jung, Han‐Sung
Abstract: Background: Six1 is a transcriptional factor that plays an important role in embryonic development. Mouse and chick embryos deficient for Six1 have multiple craniofacial anomalies in the facial bones and cartilages. Multiple Six1 enhancers have been identified, but none of them has been reported to be active in the maxillary and mandibular process. Results: We studied two Six1 enhancers in the chick neural crest tissues during craniofacial development. We showed that two evolutionarily conserved enhancers, Six1E1 and Six1E2, act synergistically. Neither Six1E1 nor Six1E2 alone can drive enhancer reporter signal in the maxillary or mandibular processes. However, their combination, Six1E, showed robust enhancer activity in these tissues. Similar reporter signal can also be driven by the mouse homolog of Six1E. Mutations of multiple conserved transcriptional factor binding sites altered the enhancer activity of Six1E, especially mutation of the LIM homeobox binding site, dramatically reduced the enhancer activity, implying that the Lhx protein family be an important regulator of Six1 expression. Conclusion: This study, for the first time, described the synergistic activation of two Six1 enhancers in the maxillary and mandibular processes and will facilitate more detailed studies of the regulation of Six1 in craniofacial development. Key Findings: Two evolutionarily conserved enhancers control Six1 expression in the maxillary and mandibular process synergistically. The synergy is also evolutionarily conserved. Lhx binding site is important for the enhancer activity.